Ultrabright Organic Dots with Aggregation‐Induced Emission Characteristics for Real‐Time Two‐Photon Intravital Vasculature Imaging. (19th August 2013) - Ding, Dan; Goh, Chi Ching; Feng, Guangxue; Zhao, Zujin; Liu, Jie; Liu, Rongrong; Tomczak, Nikodem; Geng, Junlong; Tang, Ben Zhong; Ng, Lai Guan; Liu, Bin
<x xml:space="preserve">Abstract</x> Ultrabright organic dots with aggregation‐induced emission characteristics (AIE dots) are prepared and shown to exhibit a high quantum yield, a, large two‐photon absorption cross‐section, and low in vivo toxicity. Real‐time two‐photon intravital blood vascular imaging in various tissues substantiates that the AIE dots are effective probes for in vivo vasculature imaging in a deep and high‐contrast manner. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>